(3GdefXeGJ GdOhdjIs - (3GdTGaYj(B, (3eMeO HTjQs ((3GdGScfOQjI(B:s (3efTCI GdeYGQa(B,s, 2002)
(3GdfXQjI GdYGeI hCgOGa GdJfXje GdOhdj(B:(3GdJYQja HGdefXeI GdOhdjI hCfhGYgG, CgOGa GdJfXje GdOhdj, GdefXeGJ GdOhdjI GdYGdejI(B:(3GdCee GdeJMOI, GdefXeGJ GdOhdjI GdeJNUUI, GdefXeGJ GdOhdjI GdEbdjejI(B:(3GdefXeGJ GdChQHjI,efXeI GdOhd GdCeQjcjI, efXeI GdhMOI GdCaQjbjI, LGeYI GdOhd GdYQHjIs
Keywords: (3GdCee GdeJMOIs; (3GdefXeGJ GdOhdjIs; (3efXeI GdhMOI GdEaQjbjIs